Immunotherapy in gestational trophoblastic neoplasia: advances and future directions - Zeng, Jing; Zhang, Jing; Wang, Jianzhang; Xu, Lian; Wang, Cheng; Yin, Rutie (Frontiers in Immunology, 2025)
Gestational trophoblastic neoplasia (GTN) is a rare but aggressive malignancy that follows normal or aberrant pregnancies. Until the advent of immunotherapy in 2017, surgery and chemotherapy were the standard treatment modalities, with chemotherapy remaining the cornerstone. However, chemoresistance and high-risk disease present significant challenges in managing GTN. Recent advancements in immunotherapy, particularly immune checkpoint inhibitors (ICIs), have offered new hope for managing these difficult cases. This review provides the comprehensive overview of the mechanisms underlying ICIs in GTN, and explores the potential synergy of combining ICIs with targeted therapies, such as vascular endothelial growth factor and epidermal growth factor receptor inhibitors. We also provide an overview of the latest evidence on the use of ICIs in treating GTN, focusing on their effectiveness in both low- and high-risk cases, as well as in chemorefractory settings. In addition, we discuss ongoing clinical trials, immune-related adverse events associated with ICIs, biomarker-driven approaches, immunosuppressive tumor microenvironments, and the challenges posed with ICIs resistance. The review also explores future directions, including the integration of ICIs into standard regimens, the potential for personalized treatment based on tumor biology, and the importance of fertility preservation in young patients with GTN. In conclusion, while challenges remain, immunotherapy represents a promising frontier in GTN treatment, with the potential to improve outcomes and provide a more personalized approach to care